UUM students hold recreational, beach cleaning programme in Kpg Santubong - New Sarawak, Tribune (New Sarawak Tribune, 2015)
Kuching: Twenty two distant learning students of Universiti Utara Malaysia (UUM), Kampus Kuching held a recreational and beacj- cleaning programme at Kampung Santubong.